Invariant measure of a stochastic hybrid predator–prey model with infected prey. (February 2022) - Deng, Meiling; Fan, Yingbo
Abstract: The present study formulates a stochastic predator–prey model with infected prey and regime-switching, and shows that the model has a unique stable non-boundary invariant measure which is ergodic. The theoretical results are also utilized to explore the evolution of red grouse Lagopus lagopus scoticus and fox in Scotland.